Heat Exchangers for Waste Heat Recovery - Stehlik, Petr; Jegla, Zdenek (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The economical and efficient recovery of waste heat produced by industrial processes (such as chemical and petrochemical, food, pharmaceutical, energetics) and processes and applications in the municipal sphere (such as waste incinerators, heating plants, laundries, hospitals, server rooms) are priorities and challenges. This Special Issue focuses on heat exchangers as key and essential equipment for the practical realization of these challenges. The purpose of this Special Issue is to outline the latest insights and innovative and/or enhanced solutions from the design, production, operation, and maintenance points of view of heat exchangers in different applications of effective waste heat utilization.